Approaches for the detection and analysis of antidrug antibodies to biopharmaceuticals: A review. Issue 12 (10th March 2022) - Suh, Kyungah; Kyei, Isaac; Hage, David S.
Abstract : Antibody‐based therapeutic agents and other biopharmaceuticals are now used in the treatment of many diseases. However, when these biopharmaceuticals are administrated to patients, an immune reaction may occur that can reduce the drug's efficacy and lead to adverse side‐effects. The immunogenicity of biopharmaceuticals can be evaluated by detecting and measuring antibodies that have been produced against these drugs, or antidrug antibodies. Methods for antidrug antibody detection and analysis can be important during the selection of a therapeutic approach based on such drugs and is crucial when developing and testing new biopharmaceuticals. This review examines approaches that have been used for antidrug antibody detection, measurement, and characterization. Many of these approaches are based on immunoassays and antigen binding tests, including homogeneous mobility shift assays. Other techniques that have been used for the analysis of antidrug antibodies are capillary electrophoresis, reporter gene assays, surface plasmon resonance spectroscopy, and liquid chromatography‐mass spectrometry. The general principles of each approach will be discussed, along with their recent applications with regards to antidrug antibody analysis.